Identification of Endophytic Bacterial Isolated from Oil Palm Plants with Anti-Fungal Acitvity against Ganoderma boninense - Irma Mardiah (Universitas Padjadjaran, Indonesia)
Endophytic bacteria is an excellent candidates for the biological control of pathogenic fungi in plantations. The objectives of this study were to isolate and examine anti-fungal activity of endophytic bacteria from oil palm plantations in South Kalimantan against Ganoderma boninense. This research was performed in three phases, i.e., isolation, selection, and assessment of endophytic bacteria isolates against Ganoderma boninense. A total of 126 colonies of endophytic bacteria were isolated. The result of the anti-fungal activity test with dual culture method demostrated that BKA 10 isolate had the largest inhibition zone (62.22%). Molecular identification by DNA analysis using 16S rRNA primers showed that BKA 10 is most closely related to Bacillus cereus. In conclusion, isolate with the best anti-fungal acitivity against Ganoderma boninense has the closest kinship with Bacillus cereus. Keywords: antifungal, dual culture, Bacillus cereus.